Hospital management of a public-private partnership model and a traditional model in two hospitals in Callao: Gestión hospitalaria de un modelo de asociaciones público privadas y un modelo tradicional en dos hospitales del Callao - Zanelli Reyes, Humberto D. (2022)
Introduction: The Peruvian health system usually has deciencies, This is how, since 2008, we have worked on the model of Public-Private Partnerships in Health (PPP), which seeks the best performance of the health system before being applied in the rest of similar hospital centers of the Peruvian health system. Objective: To compare the hospital management of a PPP model and a traditional model in two Essalud level II-2 hospitals. Methods: Mixed, non-experimental, and cross-sectional research carried out in two establishments, Hospital Alberto Barton Thompson (HABT) as PPP model and Hospital Luis Negreiros Vega (HLNV) as the traditional model, during the hospital management period from 2016 to 2018, six public officials and 150 external users. Hospital management was evaluated through hospital efficiency, nancial management, and user satisfaction. Results: In-hospital efficiency, the HABT presented below-standard medical-hour performance (3.31 in 2018), and lower compared to the HLNV (4.74in2018).Innancialmanagement,forbothmodelsofpublic-privatemanagement,itisagreedthat procurement plans must be carried out in advance, with common problems: ignorance of operational plans, poor epidemiological surveillance, and insufficient strengthening of skills and competencies; likewise, the APP modality spends three times more compared to the traditional modality. Conclusion: A PPP modality health facility, such as the HABT, does not seem to present better results than a traditional format facility such as the HLNV.